Effect of pyruvate kinase gene deletion on the physiology of Corynebacterium glutamicum ATCC13032 under biotin-sufficient non-glutamate-producing conditions: Enhanced biomass production - Kazunori Sawada; Masaru Wada; Takuya Hagiwara; Susumu Zen-in; Keita Imai; Atsushi Yokota (Metabolic Engineering Communications, 2015)
The effect of pyruvate kinase gene (pyk) deletion on the physiology of Corynebacterium glutamicum ATCC13032 was investigated under biotin-sufficient, non-glutamate-producing conditions. In a complex medium containing 100 g/L glucose, a defined pyk deletion mutant, strain D1, exhibited 35% enhancement in glucose consumption rate, 37% increased growth and a 57% reduction in respiration rate compared to the wild-type parent. Significant upregulation of phosphoenolpyruvate (PEP) carboxylase and downregulation of PEP carboxykinase activities were observed in the D1 mutant, which may have prevented over-accumulation of PEP caused by the pyk deletion. Moreover, we found a dramatic 63% reduction in the activity of malate:quinone oxidoreductase (MQO) in the D1 mutant. MQO, a TCA cycle enzyme that converts malate to oxaloacetate (OAA), constitutes a major primary gate to the respiratory chain in C. glutamicum, thus explaining the reduced respiration rate in the mutant. Additionally, pyruvate carboxylase gene expression was downregulated in the mutant. These changes seemed to prevent OAA over-accumulation caused by the activity changes of PEP carboxylase/PEP carboxykinase. Intrinsically the same alterations were observed in the cultures conducted in a minimal medium containing 20 g/L glucose. Despite these responses in the mutant, metabolic distortion caused by pyk deletion under non-glutamate-producing conditions required amelioration by increased biomass production, as metabolome analysis revealed increased intracellular concentrations of several precursor metabolites for building block formation associated with pyk deletion. These fermentation profiles and metabolic alterations observed in the mutant reverted completely to the wild-type phenotypes in the pyk-complemented strain, suggesting the observed metabolic changes were caused by the pyk deletion. These results demonstrated multilateral strategies to overcome metabolic disturbance caused by pyk deletion in this bacterium. Keywords: Corynebacterium glutamicum, Pyruvate kinase, Biomass production, Phosphoenolpyruvate carboxylase, Phosphoenolpyruvate carboxykinase, Malate:quinone oxidoreductase